Sex differences in cortical microstructural changes in asymptomatic individuals at risk for Alzheimer's disease: Neuroimaging / imaging and genetics. (7th December 2020) - Chance, Steven A; Torso, Mario; Chiesa, Patrizia Andrea; Lemercier, Pablo; Vergallo, Andrea; Lista, Simone; Potier, Marie‐Claude; Dubois, Bruno; Hampel, Harald; ,
Abstract: Background: The preclinical phase of Alzheimer's disease (AD) is characterized by cortical microstructural changes before the appearance of clinical symptoms. Previous studies have shown that women can present significantly faster age‐related decline than men [Filon et al., 2016; Barnes et al., 2005; Ferretti et al., 2018]. The aim of the present study was to investigate the impact of sex in whole brain cortical changes in an asymptomatic population at risk for AD. Method: A total of 167 subjects (68 males and 99 females) recruited in the Investigation of Alzheimer's Predictors in Subjective Memory Complainers (INSIGHT‐preAD) study, were included in the present work. The T1 structural and diffusion tensor imaging (DTI) scans acquired at baseline and after 24 months, were analysed to calculate 3 novel cortical diffusion measures (AngleR, PerpPD and ParlPD) [McKavanagh et al., 2019] and the mean diffusivity (MD). An independent sample t‐test was used to assess group differences in demographic, clinical and MRI volumetric values. A linear regression analysis was performed to investigate the role of sex, age and APOE genotype on baseline cortical values. The repeated measures ANOVA was used to assess cortical diffusion differences at baseline and follow‐up. Result: Men compared with women showed higher angle between the principal diffusion direction and the radial minicolumn direction across the cortex at the baseline (p=0.001). No demographic, clinical nor brain volumetric differences between men and women were detected. The linear regression analysis revealed that only sex explains differences in AngleR values (p=0.001). The repeated measures ANOVA showed a significant effect of time (p=<0.001) and a significant interaction between time and sex (p=0.013), with a higher progression rate in women compare to men. Conclusion: These findings indicate that sex has a significant effect on cortical changes and in their progression rate. The DTI measures could have a central role in enabling individual's specific characterization and may be informative for the development and assessment of potential drug targets that are specific for each subgroup.